COMMUNITY EMPOWERMENT BASED ON LOCAL POTENTIAL: A SYSTEMATIC LITERATURE REVIEW - Dwiko Rynoza Nur Rachman; Ali Roziqin; Salahudin Salahudin (DIA: Jurnal Administrasi Publik, 2022)
This study aims to find out how to empower the community by utilizing local potential. The research method used in this study is the systematic literature review paper method, where the systematic literature review method can review and identify scientific articles systematically in each process by following the steps that have been set. Through descriptive analysis by means of literature review and assistance from the VOSViewer and Mendeley software, the researchers obtained as many as 176 articles that were relevant to the topic obtained from the SCOPUS database. The results showed that there were 80 concepts identified in 152 articles. Meanwhile, the limitation of this article is that the articles reviewed only come from the SCOPUS database, so there is no comparison data from other databases such as the Web of Science. Therefore, further research can use a comparative analysis approach involving two databases, such as SCOPUS and Web of Sciences.